Consumer Experience in Purchasing Fashion Products in Indonesian E-Commerce: A Mixed-Methods Study on Customer and Supply Chain Practitioner Perspectives - Kelly Immaculata; Atika Salma; Erlinda Yunus (Journal of Consumer Sciences, 2025)
Background: Internet users in Indonesia are increasing rapidly as information and communications technology (ICT) develops. Online shopping is growing in popularity, owing to the ease of access and transactions afforded by this technology. This study extends previous research by focusing on the influence of consumer experience on purchasing fashion products. Purpose: This study aimed to explain and analyze the influence of consumer experience in purchasing fashion products through online applications on customer satisfaction and its relationship with future purchase intentions. Method: This study employed a survey involving 282 fashion product consumers, followed by interviews with three supply chain practitioners to verify the quantitative findings and gain further insights. Quantitative data were analyzed using Structural Equation Modeling (SEM), while qualitative data were analyzed based on the interviews. Findings: The results show that consumer experience significantly influences customer satisfaction, particularly regarding returnability. Customer satisfaction, in turn, improves future intentions to purchase fashion products through e-commerce. Conclusions: Consumer experience is pivotal for improving customer satisfaction and future purchase intentions in the Indonesian online fashion industry. Furthermore, practitioner perspectives offer profound insights into how operational practices and strategic decisions in e-commerce logistics contribute to customer satisfaction. Research implication: This study highlights the crucial role of consumer experience in shaping customer satisfaction and loyalty in Indonesia’s online fashion market. These findings suggest that e-commerce managers should prioritize seamless delivery, return policies, and the overall consumer experience to enhance customer retention and long-term loyalty.